1997
DOI: 10.1063/1.119246
|View full text |Cite
|
Sign up to set email alerts
|

Overdamped Josephson junctions with Nb/AlOx/Al/AlOx/Nb structure for integrated circuit application

Abstract: We present characteristics of overdamped Josephson junctions consisting of Nb/AlOx/Al/ AlOx/Nb structures. The junctions were fabricated using a well-developed Nb/AlOx/Nb-junction technology and showed well-defined Josephson characteristics at 4.2 K. The characteristic voltage Vc [the product of the critical current Ic and the effective normal resistance Rn(eff)] of junctions, which determines high-frequency performance of the junction, was in the range of 0.1–0.5 mV, and the critical current density Jc in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…junctions were fabricated using the standard trilayer technology [11]. The junction was composed of a Nb base electrode (200 nm), a lower Al layer (8 nm), a lower barrier, a middle Al layer (20 nm), an upper barrier, an upper Al layer (8 nm), and a Nb counter electrode (125 nm).…”
Section: Methodsmentioning
confidence: 99%
“…junctions were fabricated using the standard trilayer technology [11]. The junction was composed of a Nb base electrode (200 nm), a lower Al layer (8 nm), a lower barrier, a middle Al layer (20 nm), an upper barrier, an upper Al layer (8 nm), and a Nb counter electrode (125 nm).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the configuration of multilayered Josephson junctions with over-damped characteristics is also thought to be promising. In fact, over-damped junctions with a SINIS multilayered structure have already Manuscript been reported in Nb superconducting materials [11], [12]. The interlayer behaviors in SINIS junctions have already been analyzed by a microscopic model [13], in which they showed that the SINIS structures combine advantages of weak links and tunnel junctions, namely they are intrinsically shunted and have therefore non-hysteretic current-voltage characteristics.…”
Section: Introductionmentioning
confidence: 96%
“…The SINIS junctions, realized as a Nb/Al/AlO /Al/AlO / Al/Nb structure, have already been implemented in voltage standards and simple RSFQ circuits [8]- [10]; in spite of this success, their application for RSFQ circuits operating at high clock frequencies (100 GHz or higher) has been questioned because of the relatively low critical current densities and critical voltages reported in most publications (see, e.g., [6], [7], [11]). A typical critical current density for SINIS junctions is of the order of a few kA/cm or lower, which limits their use at sub-micrometer junction sizes.…”
Section: Introductionmentioning
confidence: 99%
“…A typical critical current density for SINIS junctions is of the order of a few kA/cm or lower, which limits their use at sub-micrometer junction sizes. The junctions with increased typically displayed large hysteresis [6], [11].…”
Section: Introductionmentioning
confidence: 99%